Application of Wood to Sand-slag and its Effect on Soil Strength - Budihardjo, Mochamad Arief; Chegenizadeh, Amin; Nikraz, Hamid (Elsevier BV, 2015)
In certain situations, sand is required to have extra shear strength to provide more safety, stability and support for structures. Shear strength in sand arises from friction and resistance between particles. The most common means of increasing the shear strength of sand is the cementation method. Another practice is using an additive such as slag. Some studies show that wood has also been used to improve soil strength, mostly for soft and expansive soil. However, there is limited information available on sand. Therefore, the purpose of this research is to determine whether the shear strength of a sand-slag mixture is affected by the addition of wood. Baldivis sand, a locally sourced material, was used in the experiment because it has been widely used in construction and geotechnical projects in Western Australia. The shear strength of the sand-slag-wood material was determined using an automated direct shear testing machine. There were a number of variations in test conditions, including as the amount of wood introduced into the sand-slag, the percentage of slag in the sand, the gaps between the wood, and wood orientation. The results showed that the shear strength of the sand-slag mixture tended to be enhanced by the presence of wood. The sand-slag mixture containing wood seemed to be stronger than the sand-slag without wood or the pure sand. The position of the wood also contributed to the improvement in shear strength. Placing the wood vertical to the shear direction resulted in greater strength than when the wood was positioned horizontally. From these results, it can be concluded that wood is another potential means of enhancing the shear strength of sand-slag mixture. The quantity of wood and the way it is arranged, such as distance and direction, may result in different levels of improvement to the shear strength of the sand-slag.